What matters most in institutional design for community-based rangeland management in Mongolia? - Ulambayar, Tungalag, author; Fernandez-Gimenez, Maria, author; Batjav, Batbuyan, author; Baival, Batkhishig, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
This study tested the effect of institutional design principles on social outcomes of evolving pastoral institutions in post-socialist Mongolia. Using data from 77 community-based rangeland management (CBRM) groups and 392 member households, we examined the effect of donor facilitation on institutional design. We found that donor facilitation approach significantly influenced group attributes and their external environment, but not institutional arrangements. The study confirmed that small group size, homogeneous interests, and heterogeneity of well-being are important group characteristics that predict higher levels of information diversity, leadership, and income diversity. Institutional arrangements such as the presence of sanctions, group-devised rules, frequent meetings, and recording documents increased cooperation, rules, and information diversity. Similarly, access to training and local government support provided a favorable external environment for increasing social outcomes. Furthermore, group characteristics such as dependence on livestock, homogeneity of interests, and leader legitimacy were critical for increasing social capital, livelihoods, sustainable rangeland practices, and proactive behavior of members. More frequent meetings of leaders were the most influential for these outcomes. Local government support and available donor support were associated with increased trust and norms of reciprocity, sustainable rangeland management practices, proactiveness, and livestock holdings. Lastly, group attributes and external environment influenced social outcomes of pastoral CBRMs in Mongolia more than institutional arrangements.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: commons institutions; Mongolia; institutional design; social outcomes